Image and Video Processing and Recognition Based on Artificial Intelligence (Volume II) - Park, Kang Ryoung; Lee, Sangyoun; Kim, Euntai (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on challenging issues in the field of AI-based image and video processing and recognition, including the topics of AI-based image processing, understanding, recognition, compression, and reconstruction; AI-based video processing, understanding, recognition, compression, and reconstruction; computer vision based on AI; AI-based biometrics; AI-based object detection and tracking; approaches that combine AI techniques and conventional methods for image and video processing and recognition; explainable AI (XAI) for image and video processing and recognition; generative adversarial network (GAN)-based image and video processing and recognition; and approaches that combine AI techniques and blockchain methods for image and video processing and recognition.